Multicultural education in the context of perception of educational texts - ROMANOV, I.V (Journal of Education, Technology and Computer Science, 2016)
Globalization of social relations determines the range and vector of development of main operativeforces of communicative interaction. In particular, innovative technologies and multiculturalismof the information flows become defining, which is especially important in the issues ofmodern education. There is a significant strengthening of the role of the multicultural componentof information represented in a sign form and creating a materialized mediator in the interaction ofconsciousnesses. The article deals with the questions of a multicultural aspect of educational informationin the learning process.